Trajectories of Food Choice Motives and Weight Status of Malaysian Youths during the COVID-19 Pandemic - Seok Tyug Tan (MDPI AG, 2021)
Stay-at-home orders have abruptly altered food purchasing behaviour, dietary habits, and food choice motives. Therefore, this study aims to investigate the trajectory of food choice motives and their associations with the weight status of Malaysian youths in the time of COVID-19. Socio-demographic information and anthropometric measurements were self-reported by the respondents, while the food choice motives were assessed using a validated 38-item food choice questionnaire (FCQ). Of the 1013 Malaysian youths, 48.6% gained weight due to the confinement, with an average weight gain of 3.90 ± 2.92 kg. On the other hand, 47.0% to 73.0% of the youths changed their food choice motives in the time of COVID-19. Of the 10 motives, convenience (48.5%) had the largest percentage increase, followed by weight control (47.0%) and health (45.3%). Moreover, the mean scores of health (t = −3.324, p = 0.001), convenience (t = −5.869, p < 0.001), weight control (t = −7.532, p < 0.001), natural content (t = −5.957, p < 0.001), ethical concern (t = −4.419, p < 0.001) and price (t = −3.737, p < 0.001) were significantly higher during the pandemic compared to pre-pandemic. Findings from the multinomial regression model revealed that youths highly concerned for weight control were more likely to be in the weight loss category (Adjusted odds ratio (AOR) = 1.633, Confidence Interval (CI) = 1.230–2.168, p = 0.001). Conversely, those who gained weight due to the pandemic confinement highly valued natural content in foods (AOR = 0.653, CI = 0.481–0.886, p = 0.006) when making their food choices in this unprecedented pandemic. In conclusion, Malaysian youths made healthier food choices to mitigate the risk of COVID-19 infection.